DEVELOPMENT OF LOCAL WISDOM-BASED CIVICS MODULES TO IMPROVE LEARNING OUTCOMES OF CLASS IV STUDENTS AT SD NEGERI 106206 SIDODADI - Heri Aftitah Hasibuan; Reh Bungana Beru Prangin-angin; Anita Yus (SENSEI RESEARCH CENTER, 2021)
This study aims to describe the validity, feasibility, and effectiveness of the PPKn PPKn module based on local wisdom to improve student learning outcomes on the beauty of diversity in my country. This research is research & development. While the research design used is ADDIE research. The subject of the research was one teacher for class IV and 20 students for class IV, and three expert validators. Data were collected using questionnaires, tests, and interviews. Based on the material expert validation results, an average score of 84% was obtained, then the design expert validation obtained an average score of 91%, and the linguist validation obtained an average score of 88%. When viewed from the number of three expert validators obtained an average score of 87.66%, with the module category very feasible to use. In comparison, the results of the student response questionnaire based on small group trials and field trials obtained an average score of 85%, with an excellent category. In assessing student learning outcomes, the researchers gave pre-test and post-test questions. From the pre-test and post-test, results from This can be seen from the pre-test results getting an average of 46.66 and the post-test results getting an average of 86.66%. Based on the n-gain score assessment criteria, the effectiveness of the PPKn module based on local wisdom obtained a value of 0.74 which means it is in the range of 0.70 <gs ?gs1.00, which is classified in the high category. This shows that the Civics module based on local wisdom effectively improves student learning outcomes.